Studies in Australian Tettigoniidae: The Phyllophorinae (Orthoptera: Tettigoniidae; Phyllophorinae) - Rentz, Dcf; Su, You Ning; Ueshima, Norihiro (Zootaxa, 2009)
A survey of Australian Phyllophorinae is presented. The entire fauna is represented by two species in two genera. Siliquofera grandis Blanchard, a species widely distributed in Papua New Guinea, is recorded from Iron Range, Queensland. Phyllophorella queenslandica Rentz, Su, Ueshima sp. nov. is described from Kuranda, Queensland and recorded from several localities on the Cape York peninsula. The unusual habits of the subfamily are discussed and the equally unusual karyotype of Phyllophorella queenslandica Rentz, Su, Ueshima sp. nov. is presented.